2000
DOI: 10.1046/j.1523-1747.2000.00801.x
|View full text |Cite
|
Sign up to set email alerts
|

β-Endorphin Stimulates Cytokeratin 16 Expression and Downregulates μ-Opiate Receptor Expression in Human Epidermis

Abstract: It has been reported that opioid peptides modulate the differentiation of normal human keratinocytes and that mu-opiate receptors are expressed in human epidermis. The regulation of keratinocyte differentiation is particularly important in psoriasis, and one of the markers for hyperproliferative and differentiating skin diseases is cytokeratin 16. The finding that the endogenous mu-opiate receptor ligand beta-endorphin is increased in serum of patients with psoriasis indicates that the mu-opiate system may pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
61
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 18 publications
(15 reference statements)
7
61
0
Order By: Relevance
“…The same pattern was observed in psoriatic lesional skin, i.e. µ-opiate receptor expression was significantly downregulated and cytokeratin 16 expression upregulated [4]. These results suggest that the opiate receptor system in the epidermis is functionally active and the µ-opiate receptor is involved in the pathogenesis of psoriasis, especially in terms of keratinocyte differentiation.…”
Section: Introductionsupporting
confidence: 57%
“…The same pattern was observed in psoriatic lesional skin, i.e. µ-opiate receptor expression was significantly downregulated and cytokeratin 16 expression upregulated [4]. These results suggest that the opiate receptor system in the epidermis is functionally active and the µ-opiate receptor is involved in the pathogenesis of psoriasis, especially in terms of keratinocyte differentiation.…”
Section: Introductionsupporting
confidence: 57%
“…A study (3) has shown that ␤-endorphin induces a downregulation of MOR, and that is consistent with our finding of a reduction in MOR expression in the myenteric plexus in SCID mice in which visceral pain thresholds were normalized 12 wk postreconstitution. Interestingly, as the antinociceptive effect declined at 18 wk postreconstitution, ␤-endorphin expression also declined, and there was a corresponding upregulation of MOR (22).…”
supporting
confidence: 92%
“…However, the dose of 2 to 8 mg/kg is in the range of effective antinociceptive doses for rats and therefore probably was too high to facilitate angiogenesis. The endogenous MOR and DOR agonist ␤-endorphin was reported to stimulate the expression of cytokeratin 16 (Bigliardi-Qi et al, 2000) and transforming growth factor ␤ type II (Bigliardi et al, 2003) in human skin organ cultures. Both, CK16 and TGF␤ type II receptor are not expressed in normal skin but appear in regenerating epithelial cells of the epidermis during wound healing.…”
Section: Subanalgesic Morphine To Accelerate Healing Processesmentioning
confidence: 99%